A Life in Shadow : Aim Bonpland in Southern South America, 18171858. - Bell, Stephen (Stanford University Press, 2010)
French naturalist and medical doctor Aim Bonpland (17731858) was one of the most important scientific explorers of South America in the early nineteenth century. From 1799 to 1804, he worked alongside Alexander von Humboldt as the latter carried out his celebrated research in northern South America, but he later returned to conduct his own research farther south. A Life in Shadow accounts for the entire span of Bonpland's remarkable and diverse career in South Americain Argentina, Paraguay (where he was imprisoned for nearly a decade), Uruguay, and southernmost Brazilbased on extensive arc.